2009
DOI: 10.1111/j.1467-9280.2009.02323.x
|View full text |Cite
|
Sign up to set email alerts
|

Caregiving Behavior Is Associated With Decreased Mortality Risk

Abstract: Traditional investigations of caregiving link it to increased caregiver morbidity and mortality, but do not disentangle the effects of providing care from those of being continuously exposed to an ailing loved one with serious health problems. We explored this possible confound in a national, longitudinal survey of elderly married individuals (N = 3,376). Results showed that spending at least 14 hr per week providing care to a spouse predicted decreased mortality for the caregiver, independently of behavioral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
158
2
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(185 citation statements)
references
References 31 publications
14
158
2
2
Order By: Relevance
“…The present findings are also consistent with literature that links prosocial behavior to favorable social outcomes such as peer acceptance (Layous et al, 2012), feelings of connectedness (Nelson et al, 2015), social adjustment (Crick, 1996), and eudaimonic well-being (Nelson et al, 2016), as well as to favorable health correlates including cardiovascular function and decreased mortality (Brown et al, 2003(Brown et al, , 2009. Our findings extend that literature by providing the first experimental evidence that prosocial behavior can causally impact CTRA gene expression.…”
Section: Genomic Benefits Of Prosocial Behaviorsupporting
confidence: 81%
See 2 more Smart Citations
“…The present findings are also consistent with literature that links prosocial behavior to favorable social outcomes such as peer acceptance (Layous et al, 2012), feelings of connectedness (Nelson et al, 2015), social adjustment (Crick, 1996), and eudaimonic well-being (Nelson et al, 2016), as well as to favorable health correlates including cardiovascular function and decreased mortality (Brown et al, 2003(Brown et al, , 2009. Our findings extend that literature by providing the first experimental evidence that prosocial behavior can causally impact CTRA gene expression.…”
Section: Genomic Benefits Of Prosocial Behaviorsupporting
confidence: 81%
“…Prosocial behavior can include acts directed at a specific other, such as purchasing coffee for a stranger, or individual efforts to better the world that are not directed at any specific individual, such as picking up litter. Beyond the general effects of social ties, observational epidemiology has also documented several health correlates of prosocial behavior in particular, including reduced risk of cardiovascular disease and mortality (Brown et al, 2003(Brown et al, , 2009Konrath et al, 2012;Poulin and Holman, 2013). These effects have been hypothesized to stem from neurophysiological correlates of prosocial behavior such as alterations in oxytocin and progesterone activity (Brown and Brown, 2015) or altered activity of the hypothalamus-pituitary-adrenal axis and sympathetic nervous system (Eisenberger and Cole, 2012).…”
Section: Prosocial Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…Two recent overviews, by Brown & Brown [13] and Roth et al [14], have argued for more balance, suggesting that "policy reports, media portrayals, and many research reports commonly present an overly dire picture' while ignoring alternative positive findings. It is now recognised that many caregivers report benefit from caregiving [15,16] and population-based mortality studies generally find that caregivers have reduced mortality compared with non-caregivers [17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…The responsibility for the care recipient led to personal growth (Leipold et al 2006) and provided intrinsic rewards as experienced self-gain of the caregivers (Foley et al 2002). In addition, one recently run study in the United States of America indicated that the caring for a disabled spouse more than 14 hours a week may even lead to an increased life expectancy (Brown et al 2009). …”
Section: Introductionmentioning
confidence: 99%